Analysis of Molecular Docking Chemical Content of Lime (Citrus aurantiifolia (Christm.) Swingle) Against Diabetes Mellitus Therapy Targets and Prediction of Pharmacokinetic Profiles and Toxicity - Ismah, Kadar; Supriyadi (HM Publisher, 2022)
Diabetes mellitus drugs currently available are sulfonylureas, biguanides, thiazolidines, and alpha glucoside inhibitors which are widely used to control hyperglycemia. These drugs cannot prevent complications of diabetes, and these drugs should not be used continuously because it causes undesirable pathological conditions. The essential oil in lime peel is rich in phenolics, especially flavonoids, which can prevent oxidative stress. This research was carried out computationally to determine the affinity of the compound mechanism in lime, pharmacokinetic profile, and toxicity of the chemical content of lime which is thought to have antihyperglycemic activity using chemoinformatics studies. The hardware used is an Asus laptop X441UB-GA502T Intel Core I5 – 8250 DDR 4 4GB HD 1TB VGA mix 110 2GB screen 14